A Review of “Japanese through Newspaper Articles” - Ayat Hosseini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present article introduces and evaluates the textbook “Japanese through Newspaper Articles” written by Osamu and Nobuko Mizutani which is commonly taught in “Journalistic Japanese” classes both in and outside Japan. This article reviews the book from two different points of view: first, the linguistic and pedagogical functions of the book are evaluated, and its achievements as a language textbook are criticized. Second, the cultural aspects of the book are evaluated and the image it tries to portray from Japanese society is analyzed. In order to achieve these goals, 60 real journal articles are randomly selected from Japanese press and their content is compared to that of the news articles in the book by using polarity tags.